Pregnant women’s knowledge on early orthodontic prevention – a questionnaire survey - Szalewska, Magdalena; Boryczka, Monika; Kapica, Anna; Lemejda, Justyna; Łukasik, Marta; Pietryka-Michałowska, Elżbieta; Szymańska, Jolanta (Polish Journal of Public Health, 2016)
Introduction. Ensuring proper conditions for the development of the masticatory organ of the child can prevent or reduce the incidence of malocclusion. Aim. The study aimed to assess the knowledge of mothers on selected elements of early orthodontic prevention. Material and methods. A questionnaire survey was carried out among 234 pregnant women and women in childbirth from Lower Silesia, Lublin and Lubuskie voivodships. The survey included questions about demographics of mothers, such as age, place of residence, education level, and 10 questions on selected elements of early orthodontic prevention. Results. The knowledge of mothers on the early orthodontic prevention is associated with the level of education and the place of residence – women with higher education and living in large cities have the greatest expertise in this field, although it is still inadequate in general population of women.